CD38: An Immunomodulatory Molecule in Inflammation and Autoimmunity - Piedra-Quintero, Zayda L.; Wilson, Zachary; Nava, Porfirio; Guerau-de-Arellano, Mireia (Frontiers in Immunology, 2020)
CD38 is a molecule that can act as an enzyme, with NAD-depleting and intracellular signaling activity, or as a receptor with adhesive functions. CD38 can be found expressed either on the cell surface, where it may face the extracellular milieu or the cytosol, or in intracellular compartments, such as endoplasmic reticulum, nuclear membrane, and mitochondria. The main expression of CD38 is observed in hematopoietic cells, with some cell-type specific differences between mouse and human. The role of CD38 in immune cells ranges from modulating cell differentiation to effector functions during inflammation, where CD38 may regulate cell recruitment, cytokine release and NAD availability. In line with a role in inflammation, CD38 appears to also play a critical role in inflammatory processes during autoimmunity, although whether CD38 has pathogenic or regulatory effects varies depending on the disease, immune cell, or animal model analyzed. Given the complexity of the physiology of CD38 it has been difficult to completely understand the biology of this molecule during autoimmune inflammation. In this review, we analyze current knowledge and controversies regarding the role of CD38 during inflammation and autoimmunity and novel molecular tools that may clarify current gaps in the field.